A meta-analysis of the efficacy of ureteroscopic lithotripsy and extracorporeal shock wave lithotripsy on ureteral calculi - Xu,Yahong (2014)
PURPOSE:To re-evaluated the clinic efficacy of ureteroscopic lithotripsy (URS) and extracorporeal shock wave lithotripsy (ESWL) on ureteral calculi with Cochrane systematic reviews in this paper.METHODS: We searched clinical randomized controlled trials and prospective controlled trials in databases such as Cochrane library, Medline, Springer, Elsevier Science Direct, PubMed. Pooled estimate of risk ratios (RRs), standard mean difference (SMD) with 95% confidence intervals (CIs) were used as measure of effect sizes. Summary effect estimates were also stratified by sample size, study design and study region. The overall effect sizes were derived using a random-effects model or fixed-effects model when appreciated, and meta-analysis were conducted with software RewMan 5.0.RESULTS:The meta-analysis suggested that there were significant differences of post-treatment stone free rate, repeat treatment rate, patients' satisfaction, incidence of postoperative complications, operation time and hospital stays between ESWL treatment cases and URS treatment cases. But in the sample sizes analysis, there were no significant differences of the post-treatment stone free rate and repeat treatment rate when the sample sizes were less than 100.CONCLUSIONS: Compared to the ureteroscopic lithotripsy treatment, extracorporeal shock wave lithotripsy treatment provided a significantly lower post-treatment stone free rate, but it also obviously brought out less postoperative complications, shorter operation time and hospital stays.